Jovian Injections Observed at High Latitude - Haggerty, D. K. (Geophys Res Lett, 2019)
The polar orbit of Juno at Jupiter provides a unique opportunity to observe high‐latitude energetic particle injections. We measure energy‐dispersed impulsive injections of protons and electrons. Ion injection signatures are just as prevalent as electron signatures, contrary to previous equatorial observations. Included are previously unreported observations of high‐energy banded structures believed to be remnants of much earlier injections, where the particles have had time to disperse around Jupiter. A model fit of the injections used to estimate timing fits the shape of the proton signatures better than it does the electron shapes, suggesting that electrons and protons are different in their abilities to escape the injection region. We present ultaviolet observations of Jupiter's aurora and discuss the relationship between auroral injection features and in situ injection events. We find, unexpectedly, that the presence of in situ particle injections does not necessarily result in auroral injection signatures.